PENGUATAN DIMENSI MANDIRI MELALUI SURVIVAL SKILL PRAMUKA PENGGALANG SDN BANJAR TIMUR 1 - Syamsul Arifin; Syaiful Bahri; Jamilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of survival skill activities in Scout Scouts on strengthening the independent dimension in students of SDN Banjar Timur I. This study uses a qualitative descriptive approach with additional quantitative analysis. The research design used was a case study with a sample of 30 students who actively participated in Scout Fundraising activities. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using descriptive statistics for quantitative data and thematic analysis for qualitative data. The results showed that there was a significant improvement in all indicators of self-sufficiency dimension after participating in survival skill activities. Before the activity, most of the students showed a low level of confidence, but after the activity, their confidence increased by 20%. Students' initiative, responsibility, and decision-making abilities have also experienced a significant increase. In addition, survival skills activities provide hands-on experience in facing challenges that increase a sense of responsibility and better decision-making in urgent situations. These findings indicate that Scouting activities, especially those related to survival skills, are effective in strengthening the independent dimension of elementary school students, which is in line with the goals of the Pancasila Student Profile.